Ameliorative effects of chloroform fraction of cocos nucifera L. husk fiber against cisplatin-induced toxicity in rats (2015)
Background: Cisplatin (Cis) is used in the treatment of solid tumors and is known to elicit serious side effects. Objective: The present study investigated the protective effects of chloroform fraction of Cocos nucifera husk fiber (CFCN) against Cis‑induced organs’ damage and chromosomal defect in rats. Quercetin (QUE), standard antioxidant, served as positive control. Materials and Methods: Thirty male Wistar rats were assigned into six groups and treated with corn oil (control), Cis alone, Cis + CFCN, CFCN alone, Cis + QUE, and QUE alone. QUE and CFCN were given at 50 and 200 mg/kg/day, respectively, by oral gavage for 7 days before the rats were exposed to a single dose of Cis (10 mg/kg, intraperitoneal) at the last 36 h of study. Results: Administration of Cis alone caused a significant (P < 0.05) increase in the levels of serum creatinine and urea by 72% and 70%, respectively, when compared with the control. The activity of serum aspartate aminotransferase was significantly (P < 0.05) increased while alanine aminotransferase and alkaline phosphatase were insignificantly (P > 0.05) affected in Cis‑treated rats. Furthermore, the activities of hepatic and renal catalase, superoxide dismutase, glutathione S‑transferase, glutathione peroxidase, and levels of reduced glutathione were significantly (P < 0.05) decreased in Cis‑treated rats with concomitant elevation of malondialdehyde. Cis exposure increased the frequency of micro nucleated polychromatic erythrocytes (mPCE) by 92%. Pretreatment with CFCN inhibited lipid peroxidation, enhanced the activities of some antioxidative enzymes and reduced the frequency of mPCE. Conclusions: Chloroform fraction of CFCN may protect against organs damage by Cis. Further studies are required to determine the component of the plant responsible for this activity.